Automatic Exchange of Information Review from the Perspective of its Effectives in Minimizing Tax Evasion - Chairil Anwar Pohan; Notika Rahmi; Pebriana Arimbhi; Ahmad Junaidi (Ilomata International Journal of Tax and Accounting, 2022)
This research aims to review the implementation of automatic exchange of information (AEoI) from the perspective of its effectiveness in minimizing tax evasion and to analyze the inhibiting entities and encouraging entities in AEoI in minimizing tax evasion. The research approach used in this study is a qualitative approach with data collection techniques using in-depth interviews, observation, literature/ documentation studies and source triangulation. The results of the study conclude that the Implementation of AEoI in minimizing tax evasion so far has been quite effective according to international standards, although there are still many complete data sets that have not been fulfilled by partner countries, resulting in data provided by partner countries cannot be used by the Indonesian tax authorities. However, the performance of AEoI has not yet provided optimal results in increasing tax revenue, especially in 2020, its progress has been hampered by the Covid 19 Pandemic. On the other hand, Directorate General of Taxation (DGT) still has obstacles. There are four obstacles and challenges in AEoI, namely: First, the Reciprocity of Information Exchange (Reciprocity). Second, banking tends to be resistant to data access. Third, the lack of technology that supports AEoI. Fourth, the complexity of Conversion of Tax Revenue Data. The Entity that drives this information exchange in minimizing tax avoidance is the existence of an Information Exchange System called the "Common Transmission System (CTS).